Protecting civilians during violent conflict theoretical and practical issues for the 21st century - Lovell, David W. 1956-; Primoratz, Igor (Military and defence ethics, 2012)
Examines what is being done, and what can be done, to make soldiers more aware of their responsibilities in this area under international law and the ethics of war, and more able to respond appropriately to the challenges that will confront them in the field.